The English Speaking Competency and Challenges for BIPA Teachers - Fadjar Indra Kurniawan; Iwan Jazadi (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This research aimed to determine: (1) How important English speaking ability is for BIPA teachers; (2) What English speaking macro skills should be prepared to be a BIPA teacher; (3) What obstacles BIPA teachers find in the teaching process and howÂ they solve them. This research used the qualitative method. The participants of this research were two BIPA teachers from different offices, from West Nusa Tenggara Province Language Office and Mataram Lingua Franca Institute. This research mostly used interviews to support the data of this research, while observation and documentation were used as supporting sources. The results of this research indicate that: (1) English speaking ability on A1 grade or the first grade is important because English is a bridge to connect the students to Indonesian; (2) There are five macro skills of English speaking ability that should be mastered by BIPA teachers; (3) The obstacles that mostly appear on the teaching process are based on the purpose of the learners to study Indonesian and the characteristics of each student from different countries.